STUDIES ON THE TRANSPORTATION OF LIVE CLAMS - GOPAL, T. K SRINIVASA; RAO, C V. N; PERIGREEN, P A; GOVINDAN, T K (Fishery Technology, 2017)
Live clams ( Villorita cyprinoides) collected from their natural beds were packed in different ways like dry pack, tray pack, in oxygenated water (wet pack) and depurated samples in wet pack. It was found that the packaging in l kg lots in 200 gauge polythene bags with oxygen at a temperature of 20°C could keep them live for 4 days. In tray pack without oxygen and water they can be kept alive for 3 days at 20°C. Temperature seems to be the critical factor in the transportation of live clams. At room temperature both dry and wet pack can be kept for 24h only. Depuration technique does not appear to be useful in prolonging the storage life of clams in live condition as percentage mcrtality is more at 48 h both at 20°C and room temperature compared to the non-depurated samples.